CLASSROOM-BASED ASSESSMENT LITERACY OF ENGLISH SECONDARY SCHOOL TEACHERS IN INDONESIAN CONTEXT - Dewi Aria, - (2022)
Assessing student performance is an essential part of teachers' jobs. Therefore, it is assumed that teachers are familiar with various types of assessments, especially classroom-based assessments. However, previous studies found that the majority of teachers did not have adequate knowledge and skills in assessment. Others, in a similar vein, the teachers tended to practice classroom-based assessment from a summative perspective. In responding to this situation, investigating teachers' assessment literacy levels and how they practice classroom-based assessment is necessary to conduct. This study aims to investigate English secondary school teachers' assessment literacy levels and understand how they practice classroom-based assessment. Using a mixed-method design, this study involved 105 teachers from senior high schools in Riau Province. Five teachers were chosen purposively to be involved in interviews and five teacher documents were collected to be analyzed. A Scale of Teacher Assessment Practices (STAP) by Howell (2013) was adapted to collect quantitative data which was then analyzed using descriptive statistics. Interviews and document analysis were conducted for more information in detail as qualitative data collection. The findings of this study revealed that teachers in this study were reported to have procedural and conceptual literacy levels (M = 76.08) in which the teachers understand the concepts of the classroom-based assessment and applied that knowledge in practice, but with a need to enhance knowledge and practice in identifying clear learning targets and involving students in the assessment process. Further, the teachers were found not to carry out one of the assessment functions, namely Assessment as Learning (AaL). The results of this current study suggest English teachers write specific, concrete, and achievable learning targets in student-friendly language to make them easier to understand what they will learn and can do at the end of the lesson and hence assess themselves on what they are in a learning and what they have learned.